Ultrasound mediated delivery of quantum dots from a proof of concept capsule endoscope to the gastrointestinal wall - Fraser Stewart (Nature Portfolio, 2021)
Abstract Biologic drugs, defined as therapeutic agents produced from or containing components of a living organism, are of growing importance to the pharmaceutical industry. Though oral delivery of medicine is convenient, biologics require invasive injections because of their poor bioavailability via oral routes. Delivery of biologics to the small intestine using electronic delivery with devices that are similar to capsule endoscopes is a promising means of overcoming this limitation and does not require reformulation of the therapeutic agent. The efficacy of such capsule devices for drug delivery could be further improved by increasing the permeability of the intestinal tract lining with an integrated ultrasound transducer to increase uptake. This paper describes a novel proof of concept capsule device capable of electronic application of focused ultrasound and delivery of therapeutic agents. Fluorescent markers, which were chosen as a model drug, were used to demonstrate in vivo delivery in the porcine small intestine with this capsule. We show that the fluorescent markers can penetrate the mucus layer of the small intestine at low acoustic powers when combining microbubbles with focused ultrasound during in vivo experiments using porcine models. This study illustrates how such a device could be potentially used for gastrointestinal drug delivery and the challenges to be overcome before focused ultrasound and microbubbles could be used with this device for the oral delivery of biologic therapeutics.